2021
DOI: 10.2169/internalmedicine.6262-20
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Embolism Associated with Calcified Amorphous Tumor: A Review of Cerebral Infarction Cases

Abstract: Calcified amorphous tumor (CAT) is a non-neoplastic tumor composed of calcified nodules consisting of amorphous fibrous material, and it may eventually cause cerebral infarction (CI). We experienced a 67-year-old woman with CAT who had recurrent CI. After excision of the CAT, the CI did not show recurrence. A review of previous papers on CI due to CAT in Pubmed revealed that 7 of 13 studies originated in Japan and that CI can occur even with small CAT. Surgical treatment is recommended to prevent CI recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Embolic events typically involve the brain or retina 10. Rare clinical presentations include multiple cardiac masses,11 presentation in the neonatal period,12 and infected CAT 13…”
Section: Discussionmentioning
confidence: 99%
“…Embolic events typically involve the brain or retina 10. Rare clinical presentations include multiple cardiac masses,11 presentation in the neonatal period,12 and infected CAT 13…”
Section: Discussionmentioning
confidence: 99%
“…CAT is an extremely rare non-neoplastic intracardiac tumor composed of calcified nodules and amorphous materials and is most commonly found in the mitral valve [1]. A recent study reported that CAT is usually associated with heart valve disease, hemodialysis, MAC, and diabetes mellitus [4].…”
Section: Discussionmentioning
confidence: 99%
“…A calcified amorphous tumor (CAT) is a rare non-neoplastic tumor that commonly requires surgical intervention owing to embolic events [1]. Moreover, caseous mitral annular calcification (MAC) is a rare pathology that causes serious embolic events and is sometimes associated with CAT [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It is not life-threatening itself, yet it is found to cause embolization. A previous study has reported pulmonary or systemic embolization in 31% of their CAT cases [ 2 ], and another study has reported approximately 20 cases of cerebral infarctions from CAT [ 3 ].…”
Section: Introductionmentioning
confidence: 99%